Pengaruh Model Pembelajaran Group Investigation terhadap Hasil Belajar Siswa - Agus, Agus Rahmat; Gumilar, Gugum; Srigustini, Astri (Civiliza Publishing, Indonesia., 2024)
The low learning outcomes of class XI students at SMAN 3 Tasikmalaya in economics prompted the author to conduct this research. The purpose of this study was to determine the effect of the group investigation learning model on student learning outcomes. By using quantitative research methods, quasi-experimental methods with non-equivalent control group design. Class XI IPS 1 as the experimental class and class XI IPS 2 as the control class are the research samples used in the study. Based on the results of hypothesis testing, the sig. (2-tailed) value is 0.000 and more than (<0.005). That there is a positive influence between the group investigation learning model on learning outcomes. Likewise, the average score of the experimental class learning outcomes is greater than the control class. So, it can be concluded that the application of the group investigation learning model in the subject of economics, international trade material, has a positive effect on student learning outcomes.